A correlation between shoulder laxity and interfering pain in competitive swimmers - McMaster, W. C.; Roberts, A.; Stoddard, T. (The American Journal of Sports Medicine, 1998)
Shoulder pain in the swimming athlete that interferes with effective training is serious and may result in decreased performance. Based on the hypothesis that shoulder laxity is an important factor in shoulder pain, this study of 40 senior national and elite swimmers was undertaken. A questionnaire identified those athletes currently suffering from such pain. Shoulder laxity was assessed using standard clinical tests, from which a laxity score was derived. A statistically significant correlation was identified between the shoulder laxity score and the presence of interfering shoulder pain, confirming the hypothesis of the study. These results have direct implications for training the symptomatic athlete.